LEGAL PROTECTION OF THE ENVIRONMENT IN UKRAINE: CURRENT STATE AND PROSPECTS - Trotsiuk, Nina; Hrabovsky, Hlib (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2023)
Purpose: to investigate the concept of "legal protection of the natural environment", to analyze the current state and to determine the prospects for improving the legal protection of the natural environment on the way to European integration in the field of environmental protection. Methods: general scientific and special legal methods of scientific knowledge are applied, in particular: system-structural method, observation method, generalization method, methods of analysis and synthesis. Results: on the basis of the study of legal norms and provisions of scientific works, a terminological analysis was carried out and the author’s definition of the definition "legal protection of the natural environment" was provided. It was concluded that despite a number of positive steps in ensuring state policy in the field of environmental protection, in Ukraine in the near future it is necessary to carry out reforms in such areas as: legal responsibility for environmental violations; environmental control; environmental monitoring. Discussion: in the conditions of martial law, an urgent issue is not only the adoption of normative legal acts, but also the adoption of a set of measures by state authorities. It is emphasized that a lot has already been done in this direction in Ukraine, namely: 1) a number of normative legal acts have been adopted; 2) the National Council for the Recovery of Ukraine from the Consequences of the War was created; 3) the "Environmental safety" section of the project of the National Recovery Plan of Ukraine was developed; 4) 7 methods for determining damage to the natural environment were developed; 5) an agreement was concluded regarding Ukraine’s participation in the Environment and Climate Action Program (LIFE Program), etc.